PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII - Harahap, Nur Aisiyah Fazariah (Departemen Matematika, 2023)
Problem solving ability was one of learning mathematics goals goals that have to achieved by students. However, in the real skills of mathematical problem solving by students in schools are still lack. One solution to finish these problems was to use the model of Problem Based Learning. The ultimate goal of this research was to find out whether the skill of mathematical problem solving of students who studied with the Problem Based Learning model were more good than students who studied with the model learning in Direct for class VIII MTsN 1 Padangsidimpuan. The research type used was nonequivalent posttest-only control group design. The research population were students of class VIII at MTsN 1 Padangsidimpuan. Sampling was carried out using non-random sampling (non-random sample) with purposive sampling technique by assigning class VIII 1 as the group for experimental and VIII 2 as the group for control. Based on the analysis of Problem Solving Ability test data, P-value = 0.00 is obtained with a level in significant (α = 0.05), because the P-value , then is rejected. The conclusion obtained is that students who learn with the model of Problem Based Learning was more good than those who learn with the model of learning in direct for class VIII MTsN 1 Padangsidimpuan.Keywords - Problem Based Learning, Mathematical Problem Solving Ability